IOT-enabled framework for monitoring carbon emissions in the materialization phase of modular integrated construction - Li, Clyde Zhengdao; Deng, Yiqian; Wu, Hengqin; Tam, Vivian W. Y.; Le, Khoa N.; Guo, Shan (Journal of Civil Engineering and Management, 2026)
The potential of Modular Integrated Construction (MiC) to reduce carbon emissions (CEs) has led to increased attention on developing rigorous monitoring systems. Existing methods predominantly capture CEs of isolated MiC stages, overlooking nuances of arrangeable and reusable activities, thus hindering effective CE control measures. To overcome this limitation, this study develops an Internet of Things (IoT)-enabled framework for monitoring CEs of MiC, specifically focusing on the materialization phase, integrating across various MiC stages and facilitating detailed monitoring of CEs associated with arrangeable and reusable activities. This study builds up a CE measurement model tailored to the MiC materialization phase, providing a computational basis for a subsequent monitoring framework. By leveraging IoT technology, the framework is evaluated through case studies to confirm its feasibility and efficacy. The results indicate that the framework enabled improved monitoring capabilities, and the CEs of many MiC activities are successfully integrated into the system. The case study analysis demonstrates that the system’s feedback-driven adjustments achieved a CE reduction of 732.04 metric tons.